MicroRNA-365 regulates human cardiac action potential duration - Esfandyari, Dena; Idrissou, Bio Maria Ghéo; Hennis, Konstantin; Avramopoulos, Petros; Dueck, Anne; El-Battrawy, Ibrahim; Grüter, Laurenz; Meier, Melanie Annemarie; Näger, Anna Christina; Ramanujam, Deepak; Dorn, Tatjana; Meitinger, Thomas; et al. (Nature Communications, 2022)
Abnormalities of ventricular action potential cause malignant cardiac arrhythmias and sudden cardiac death. Here, we aim to identify microRNAs that regulate the human cardiac action potential and ask whether their manipulation allows for therapeutic modulation of action potential abnormalities. Quantitative analysis of the microRNA targetomes in human cardiac myocytes identifies miR-365 as a primary microRNA to regulate repolarizing ion channels. Action potential recordings in patient-specific induced pluripotent stem cell-derived cardiac myocytes show that elevation of miR-365 significantly prolongs action potential duration in myocytes derived from a Short-QT syndrome patient, whereas specific inhibition of miR-365 normalizes pathologically prolonged action potential in Long-QT syndrome myocytes. Transcriptome analyses in these cells at bulk and single-cell level corroborate the key cardiac repolarizing channels as direct targets of miR-365, together with functionally synergistic regulation of additional action potential-regulating genes by this microRNA. Whole-cell patch-clamp experiments confirm miR-365-dependent regulation of repolarizing ionic current Iks. Finally, refractory period measurements in human myocardial slices substantiate the regulatory effect of miR-365 on action potential in adult human myocardial tissue. Our results delineate miR-365 to regulate human cardiac action potential duration by targeting key factors of cardiac repolarization.
Gesehen am 21.03.2023